State the basic principle of resolution method for both proposition and predicates
Answers
1. Implications (I):
φ ⇒ ψ → ¬φ ∨ ψ
φ ⇐ ψ → φ ∨ ¬ψ
φ ⇔ ψ → (¬φ ∨ ψ) ∧ (φ ∨ ¬ψ)
2. Negations (N):
¬¬φ → φ
¬(φ ∧ ψ) → ¬φ ∨ ¬ψ
¬(φ ∨ ψ) → ¬φ ∧ ¬ψ
3. Distribution (D):
φ ∨ (ψ ∧ χ) → (φ ∨ ψ) ∧ (φ ∨ χ)
(φ ∧ ψ) ∨ χ → (φ ∨ χ) ∧ (ψ ∨ χ)
φ ∨ (φ1 ∨ ... ∨ φn) → φ ∨ φ1 ∨ ... ∨ φn
(φ1 ∨ ... ∨ φn) ∨ φ → φ1 ∨ ... ∨ φn ∨ φ
φ ∧ (φ1 ∧ ... ∧ φn) → φ ∧ φ1 ∧ ... ∧ φn
(φ1 ∧ ... ∧ φn) ∧ φ → φ1 ∧ ... ∧ φn ∧ φ
4. Operators (O):
φ1 ∨ ... ∨ φn → {φ1, ... , φn}
φ1 ∧ ... ∧ φn → {φ1}, ... , {φn}
As an example, consider the job of converting the sentence (g ∧ (r ⇒ f)) to clausal form. The conversion process is shown below.
g ∧ (r ⇒ f)
I g ∧ (¬r ∨ f)
N g ∧ (¬r ∨ f)
D g ∧ (¬r ∨ f)
O {g}
{¬r, f}
As a slightly more complicated case, consider the following conversion. We start with the same sentence except that, in this case, it is negated.
¬(g ∧ (r ⇒ f))
I ¬(g ∧ (¬r ∨ f))
N ¬g ∨ ¬(¬r ∨ f)
¬g ∨ (¬¬r ∧ ¬f)
¬g ∨ (r ∧ ¬f)
D (¬g ∨ r) ∧ (¬g ∨ ¬f)
O {¬g,r}
{¬g, ¬f}